Characterization of roof runoff microbial quality in four U.S. cities with varying climate and land use characteristics. (15th October 2022) - Alja'fari, Jumana; Sharvelle, Sybil; Brinkman, Nichole E.; Jahne, Michael; Keely, Scott; Wheaton, Emily A.; Garland, Jay; Welty, Claire; Sukop, Michael C.; Meixner, Thomas
Highlights: Culture and molecular methods were used to examine roof runoff microbial quality. The impact of several factors on roof runoff microbial quality was explored. Salmonella spp., Campylobacter spp., and Giardia were found in roof runoff. The occurrence of potential pathogens is correlated with meteorological parameters. Assessment of microbial quality will inform treatment targets based on end use. Abstract: Roof runoff has the potential to serve as an important local water source in regions with growing populations and limited water supply. Given the scarcity of guidance regulating the use of roof runoff, a need exists to characterize the microbial quality of roof runoff. The objective of this 2-year research effort was to examine roof runoff microbial quality in four U.S. cities: Fort Collins, CO; Tucson, AZ; Baltimore, MD; and Miami, FL. Seven participants, i.e., homeowners and schools, were recruited in each city to collect roof runoff samples across 13 precipitation events. Sample collection was done as part of a citizen science approach. The presence and concentrations of indicator organisms and potentially human-infectious pathogens in roof runoff were determined using culture methods and digital droplet polymerase chain reaction (ddPCR), respectively. The analyzed pathogens included Salmonella spp ., Campylobacter spp ., Giardia duodenalis, and Cryptosporidium parvum . Several factors were evaluated to study their influence on the presence of potentially human-infectious pathogens including the physicochemical characteristics (total suspended solids, volatile suspended solids, total dissolved solids, chemical oxygen demand, and turbidity) of roof runoff, concentrations of indicator organisms, presence/absence of trees, storm properties (rainfall depth and antecedent dry period), percent of impervious cover surrounding each sampling location, seasonality, and geographical location. E. coli and enterococci were detected in 73.4% and 96.2% of the analyzed samples, respectively. Concentrations of both E. coli and enterococci ranged from <0 log10 to >3.38 log10 MPN/100 mL. Salmonella spp . invA, Campylobacter spp . ceuE, and G. duodenalis β – giardin gene targets were detected in 8.9%, 2.5%, and 5.1% of the analyzed samples, respectively. Campylobacter spp . mapA and C. parvum 18S rRNA gene targets were not detected in any of the analyzed samples. The detection of Salmonella spp . invA was influenced by the geographical location of the sampling site (Chi-square p -value < 0.001) as well as the number of antecedent dry days prior to a rain event ( p -value = 0.002, negative correlation). The antecedent dry period was negatively correlated with the occurrence of Campylobacter spp . ceuE as well ( p -value = 0.07). On the other hand, the presence of G. duodenalis β–giardin in roof runoff was positively correlated with rainfall depth ( p -value = 0.05). While physicochemical parameters and impervious area were not found to be correlated with the presence/absence of potentially human-infectious pathogens, significant correlations were found between meteorological parameters and the presence/absence of potentially human-infectious pathogens. Additionally, a weak, yet significant positive correlation, was found only between the concentrations of E. coli and those of Giardia duodenalis β-giardin . This dataset represents the largest-scale study to date of enteric pathogens in U.S. roof runoff collections and will inform treatment targets for different non-potable end uses for roof runoff. However, the dataset is limited by the low percent detection of bacterial and protozoan pathogens, an issue that is likely to persist challenging the characterization of roof runoff microbial quality given sampling limitations related to the volume and number of samples. Graphical abstarct: Image, graphical abstract